Reinforcement of V2O5 nanoparticle in polyaniline to improve the optical and UV- shielding properties - Yugesh Singh Thakur; Aman Deep Acharya; Sakshi Sharma; Bhawna (Results in Optics, 2023)
The aim of the study is to fulfil the prerequisite of the scientific community for the development of UV protective materials, especially UV shielding coatings with visible transparency but block plentiful UV light. The present study contributed to the same approach by preparing conducting polymer nanocomposites of V2O5: PANI by polymerization of V2O5 with PANI using ammonium persulphate as an oxidant. Here, we report the UV-shielding efficiency and visible light transmittance of V2O5: PANI nanocomposites where V2O5 acts as a UV absorber. UV–visible study shows that different optical parameters changed considerably after doping and facilitate UV shielding efficiency of the prepared nanocomposites in the area of interest. The weight concentration of 30% V2O5 in the PANI matrix showed a 93% increase in UV shielding efficiency with respect to PANI in the UVB region. Distinct changes including red shift, narrowing of the band gap, better polarizability, tuned refractive index as well as dissipation factor could provide valuable insight into the design and development of new and superior UV shielding materials.